'Saying goodbye' during the COVID-19 pandemic: A document analysis of online newspapers with implications for end of life care. (July 2021) - Selman, Lucy E; Sowden, Ryann; Borgstrom, Erica
Background: News media create a sense-making narrative, shaping, reflecting and enforcing cultural ideas and experiences. Reportage of COVID-related death and bereavement illuminates public perceptions of, and responses to, the COVID-19 pandemic. Aim: We aimed to explore British newspaper representations of 'saying goodbye' before and after a COVID-related death and consider clinical implications. Design: Document analysis of UK online newspaper articles published during 2 week-long periods in March–April 2020. Data sources: The seven most-read online newspapers were searched: The Guardian, The Daily Mail, The Telegraph, The Mirror, The Sun, The Times and The Metro. Fifty-five articles discussed bereavement after a human death from COVID-19, published during 18/03–24/03/2020 (the UK's transition into lockdown) or 08/04–14/04/2020 (the UK peak of the pandemic's first wave). Results: The act of 'saying goodbye' (before, during and after death) was central to media representations of COVID bereavement, represented as inherently important and profoundly disrupted. Bedside access was portrayed as restricted, variable and uncertain, with families begging or bargaining for contact. Video-link goodbyes were described with ambivalence. Patients were portrayed as 'dying alone' regardless of clinician presence. Funerals were portrayed as travesties and grieving alone as unnatural. Articles focused on what was forbidden and offered little practical guidance. Conclusion: Newspapers portrayed COVID-19 as disruptive to rituals of 'saying goodbye' before, during and after death. Adaptations were presented as insufficient attempts to ameliorate tragic situations. More nuanced and supportive reporting is recommended. Clinicians and other professionals supporting the bereaved can play an important role in offering alternative narratives.